Serviço de referência digital: uma análise apoiada em agentes de interface - Moreno, Patrícia da Silva [UNESP] (2005)
The electronic environment for the dispose of information is frequently incorporating the services offered by the libraries, aiming to provide means to find information and documents in electronic nets. However, many users have difficulties in the interaction with certain interfaces, which turns the search for information uninteresting and, most of the time, stressful. That way, alternatives are being searched to turn the human-computer interfaces more friendly and intelligent. The development and use of interface agent systems are good alternatives to minimize this type of problem. These systems function to interact with the user, as if they were characters that help in the accomplishment of certain tasks. In that sense, the objective of this research is to analyze and develop an interface agent that acts as a reference agent in a simulated website of a library, offering a personalized search service starting from the user's relationships with a digital system. The interface agent, having the information provided by the users, will build a search strategy that determines the significant words of a text presented by the user and will act as a researcher in catalogs of available libraries on Internet and in the Google index in order to offer answers to the solicitations. With the application of the interface agent the author intends to evaluate the performance of this type of software as a facilitator of the user's interaction with available collections, through digital catalogs, not as a mere illustration, but as a personal assistant in the information search process, as well as to verify through experiments with the prototype, based on the heuristic evaluation methodology, which actions should be taken for the correction of mistakes that affect the interface usability, confirming the hypothesis of effectiveness of a system of that nature... (Complete abstract, click electronic address below)